The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.gerinurse.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Trends in COVID-19 cases, deaths, and staffing shortages in US nursing homes by rural and urban status

Abstract: The purpose of the study was to examine trends in COVID-19 cases, related deaths, and staffing shortages in nursing homes (NH) by rural and urban status from May 2020 to Feb 2021. Generalized linear mixed models with state-fixed effects were used to estimate the interaction effect of study period and rural/urban status on having at least: one COVID-19 case, one related death, and/or at least one week of staffing shortage using the NH COVID-19 data spanning the 40-week period. The findings revealed shortages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…One example can be seen with the comparison of rural versus urban nursing home establishments. Though rurality itself was not associated with COVID-19 infections or related deaths, a study involving the early pandemic period revealed that there was a higher degree of volatility in staffing shortages in rural nursing homes compared to their urban counterparts [ 40 ]. While rural nursing homes experienced a higher proportion of staffing shortages until mid-November 2020, staffing shortages in urban nursing homes were relatively stable over the same period, despite fluctuations in COVID-19 case volume.…”
Section: Staffing Structure and Workforce Alterationsmentioning
confidence: 99%
“…One example can be seen with the comparison of rural versus urban nursing home establishments. Though rurality itself was not associated with COVID-19 infections or related deaths, a study involving the early pandemic period revealed that there was a higher degree of volatility in staffing shortages in rural nursing homes compared to their urban counterparts [ 40 ]. While rural nursing homes experienced a higher proportion of staffing shortages until mid-November 2020, staffing shortages in urban nursing homes were relatively stable over the same period, despite fluctuations in COVID-19 case volume.…”
Section: Staffing Structure and Workforce Alterationsmentioning
confidence: 99%
“…Further, we did not specifically examine differences that might be present in rural as compared with urban settings despite the fact that staffing shortages and skill mix issues and COVID cases/deaths may differ by rural and urban location. 50 We focused primarily on frontline nursing staff rather than other personnel or administration because of their routine and prolonged proximity to residents during the provision of care as compared to other NH staff. Finally, this scan was conducted prior to the availability of COVID vaccine.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 9 Moreover, many of these nursing home studies looked at primarily urban as opposed to rural NH populations. 10 , 11 This report analyzes the effect of prior vaccination of NH residents during recent outbreaks of SARS‐CoV‐2 in NHs in rural Manitoba, Canada. The dose‐response effect of mRNA vaccine in protection from infection was compared.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies on vaccine efficacy in NHs were performed prior to the emergence of the BA.2 variant of SARS‐CoV‐2 (Omicron) as the dominant strain, and before a third vaccine dose was recommended 2–5,9 . Moreover, many of these nursing home studies looked at primarily urban as opposed to rural NH populations 10,11 . This report analyzes the effect of prior vaccination of NH residents during recent outbreaks of SARS‐CoV‐2 in NHs in rural Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%